Feeling exclusion: religious conflict, exile and emotions in early modern Europe - Tarantino, Giovanni; Zika, Charles (Routledge, 2019)
"Feeling Exclusion investigates the emotional experience of exclusion at the heart of the religious life of persecuted and exiled individuals and communities in early modern Europe"--